Intraoral Foreign Body-Type Giant Cell Reaction in a Sjögren’s Syndrome Patient: An Immunohistochemical Analysis - Forero, Brenda Carolina Pattigno; Reyes, Magdalena Raquel Torres; Posantes, Gabriela Esperanza Maradiaga; de Almeida, Isabella Victoria; Martins, Karina Helen; Bufalino, Andreia [UNESP]; León, Jorge Esquiche (Springer Nature, 2024)
Sjögren’s syndrome (SS) is a chronic autoimmune disease characterized by lymphocytic infiltration that mainly affects the salivary and lacrimal glands, causing sicca symptoms. Non-infectious granulomatous inflammation affecting the salivary glands is rare, and it may be caused by duct obstruction associated with mucus extravasation. A 63-year-old female patient, with primary SS diagnosis 19 years ago, was referred presenting a nodular mass on the buccal mucosa 1 week ago. Microscopic analysis revealed focal lymphocytic sialadenitis and an exuberant lymphoplasmacytic infiltrate containing in the central part a foreign body-type giant cell reaction, permeated by numerous residual salivary gland ducts. Polarizing microscopy did not identify foreign material. Grocott-Gomori, acid-fast bacilli and Gram stains were negative. However, periodic acid-Schiff and mucicarmine stains revealed positivity in several multinucleated giant cells (MGC), adjacent macrophages and extracellular environment, consistent com mucus extravasation origin. Immunohistochemical analysis revealed strong positivity for CD68, CD163 and CD11c, highlighting MGC and macrophages, permeated by numerous T cells, B cells and plasma cells, whereas pan-CK and EMA evidenced residual salivary gland ducts. In the current case, mucus extravasation is a probable cause of foreign body-type giant cell reaction, suggesting a possible relationship with immune mechanisms of SS involved in its pathogenesis.
Keywords: Focal lymphocytic sialadenitis; Foreign body-type giant cell reaction; Non-infectious granulomatous inflammation; Sjögren’s syndrome